Incisor agenesis: paradigm shift. A study of an orthodontic population. Clinical cases. (2nd September 2015) - Poulet, H.; Poulet, C.; Poulet, C.
Abstract : Our study among an orthodontic population of 1, 095 patients indicates that 9% of the subjects have at least one agenesis (3% for maxillary lateral or mandibular central/lateral incisors). Regarding possible treatments, we evaluated the different solutions from the less invasive to the most invasive: simple space closure, space closure with laminated veneers, space opening with a cantilevered bonded bridge, space opening with implant. Recent advances in biomimetic dentistry suggest that now is the time for a paradigm shift.